2018
DOI: 10.2217/pgs-2018-0079
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity Reactions to Nonsteroidal Anti-Inflammatory Drugs: An Update on Pharmacogenetics Studies

Abstract: Nonsteroidal anti-inflammatory drugs are the medications most frequently involved in hypersensitivity reactions to drugs. These can be induced by specific immunological and nonimmunological mechanisms, being the latter the most frequent. The nonimmunological mechanism is related to an imbalance of inflammatory mediators, which is aggravated by the cyclooxygenase inhibition. Genetic studies suggest that multiples genes and additional mechanisms might be involved. The proposals of this review is summarize the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…In the clinical description of this group, several entities have been included that clearly represent well-differentiated forms 3. These have been described in detail in a previous section of this review and reported elsewhere 14,17,54,55. The combination of both NERD plus NECD has been reported but much more frequent than NERD are those with mixed reactions.…”
Section: Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical description of this group, several entities have been included that clearly represent well-differentiated forms 3. These have been described in detail in a previous section of this review and reported elsewhere 14,17,54,55. The combination of both NERD plus NECD has been reported but much more frequent than NERD are those with mixed reactions.…”
Section: Impactmentioning
confidence: 99%
“…The combination of both NERD plus NECD has been reported but much more frequent than NERD are those with mixed reactions. We prefer this term to blended reactions, though it is still pending a defined nomenclature that is awaiting further discussion and consensus agreements 14,17. Clinical data in children and adolescents point in this direction 22,134.…”
Section: Impactmentioning
confidence: 99%
“…NSAIDs intake brings about an imbalance in the inflammatory mediators' production in individuals who manifest cross-intolerant reactions to these drugs by mechanisms that are not fully understood [53]. Hence, an increasing number of studies support the hypothesis that additional pathways may contribute toward the underlying mechanisms of DHRs to NSAIDs [54,55].…”
Section: Nonspecific Immunological Reactionsmentioning
confidence: 99%
“…Most of aspirin-induced delayed hypersensitivity reactions are severe, such as DIHS/DRESS (drug-induced hypersensitivity syndrome/drug reaction with eosinophilia and systemic symptoms), AGEP (acute generalized exanthematous pustulosis), and less frequent TEN/SJS (Stevens-Johnson syndrome/toxic epidermal necrolysis). 4 Mechanically, aspirin-induced delayed hypersensitivity is T cell-dependent. 5 Aspirin-induced thrombocytopenia has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The immunological mechanisms underlying drug-induced thrombocytopenia can be divided into six types according to the types of antigens. 9 In the case, the mechanisms underlying the immune impairment induced by platelet IIb/IIIa and Ia/ IIa antibodies (IgG) was not clear. We speculate that aspirin, a soluble drug, induced the production of plateletspecific antibodies, namely platelet IIb/IIIa and Ia/IIa antibodies, and accelerated the clearance of platelets and thus leading to thrombocytopenia.…”
mentioning
confidence: 96%